Cell fusion induced by a fusion-active form of human cytomegalovirus glycoprotein B (gB) is inhibited by antibodies directed at antigenic domain 5 in the ectodomain of gB - Reuter, Nina; Kropff, Barbara; Schneiderbanger, Julia; Alt, Mira; Krawczyk, Adalbert; Sinzger, Christian; Winkler, Thomas; Britt, William J.; Mach, Michael; Thomas, Marco (Journal of Virology, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen that can cause severe clinical disease in allograft recipients and infants infected in utero. Virus-neutralizing antibodies defined in vitro have been proposed to confer protection against HCMV infection, and the virion envelope glycoprotein B (gB) serves as a major target of neutralizing antibodies. The viral fusion protein gB is nonfusogenic on its own and requires glycoproteins H (gH) and L (gL) for membrane fusion, which is in contrast to requirements of related class III fusion proteins, including vesicular stomatitis virus glycoprotein G (VSV-G) or baculovirus gp64. To explore requirements for gB's fusion activity, we generated a set of chimeras composed of gB and VSV-G or gp64, respectively. These gB chimeras were intrinsically fusion active and led to the formation of multinucleated cell syncytia when expressed in the absence of other viral proteins. Utilizing a panel of virus-neutralizing gB-specific monoclonal antibodies (MAbs), we could demonstrate that syncytium formation of the fusogenic gB/VSV-G chimera can be significantly inhibited by only a subset of neutralizing MAbs which target antigenic domain 5 (AD-5) of gB. This observation argues for differential modes of action of neutralizing anti-gB MAbs and suggests that blocking the membrane fusion function of gB could be one mechanism of antibody-mediated virus neutralization. In addition, our data have important implications for the further understanding of the conformation of gB that promotes membrane fusion as well as the identification of structures in AD-5 that could be targeted by antibodies to block this early step in HCMV infection. IMPORTANCE HCMV is a major global health concern, and antiviral chemotherapy remains problematic due to toxicity of available compounds and the emergence of drug-resistant viruses. Thus, an HCMV vaccine represents a priority for both governmental and pharmaceutical research programs. A major obstacle for the development of a vaccine is a lack of knowledge of the nature and specificities of protective immune responses that should be induced by such a vaccine. Glycoprotein B of HCMV is an important target for neutralizing antibodies and, hence, is often included as a component of intervention strategies. By generation of fusion-active gB chimeras, we were able to identify target structures of neutralizing antibodies that potently block gB-induced membrane fusion. This experimental system provides an approach to screen for antibodies that interfere with gB's fusogenic activity. In summary, our data will likely contribute to both rational vaccine design and the development of antibody-based therapies against HCMV.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Antibodies; Cell-cell fusion; Glycoprotein B; Herpesvirus; Human cytomegalovirus